Greenness of extraction procedures involving biochar-based sorbents for organic compounds - Francesca Merlo; Andrea Speltini; Antonella Profumo (Advances in Sample Preparation)
In the field of green sample preparation, new challenges are emerging for guaranteeing sustainability of analytical procedures and remarkable efforts have been made to develop materials from natural and/or renewable sources. In such a scenario, biochar is emerging as alternative sorbent with low economic and environmental impact. It is a carbon-rich material derived from the thermochemical conversion of biomass and waste and endowed with excellent textural properties such as high specific surface area and meso‑ and microporosity, and functional groups that are fundamental for the sorption behaviour, a key point in the analytical performance of biochar. These outstanding properties generated a growing interest in the use of biochar-based sorbents in sample preparation. In this context, this review provides an overview of the last 4-year applications of biochar in extraction techniques through an evaluation of greenness of the sample preparation procedures. At this purpose, two metric tools specific for the sample preparation, as AGREEprep and Sample Preparation Metric of Sustainability (SPMS), have been selected to give comprehensive evaluations about greenness, considering multiple criteria but with different weights and intervals in the parameters. Indeed, the papers here reviewed received in SPMS scores ranging from 5.16 to 10, and in AGREEprep from 0.16 to 0.7, evidencing there is space for improving extraction procedures involving biochar-based sorbents.